Designing Web site images: A practical guide - Gene Berryhill (Delmar, 2000)
This books covers the creation and handling of graphics for the World Wide Web, including image management strategies, compression, palettes, graphic creation and manipulation, conversion, working with display text, simple animations, and Photoshop's "onionkinning" techniques for animation.